Cualificación de la práctica docente en el área de matemáticas con apoyo de TIC (2017)
The present research aims to analyze, reflect and transform the educational practice of the assistant math teacher from sixth grade of the Departmental Rural Educational Institution (I.E.R.D.) Laguna Senas Peñas, in the municipality of Cucunubá in the department of Cundinamarca. The foregoing taking into account that when observing the environment, context and educational practice it was identified the need to carry out a pedagogical innovation that will lead to the transformation of it. By the other side, critical paradigm was chosen with a research-action design, which allows a process of diagnosis, reflection, planning and execution, whose purpose is to improve the educational practice, recognizing that there is no perfect practice and that there will always be some aspect to improve or modify. Three instruments were selected for data collection: focus and starting groups, class observation and field diaries coming from teachers and students. With these, valuable information was collected...